Students Reading Comprehension Strategy: Directed Reading Thinking Activity (DRTA) - Rahman, Wiwiek Zulfiana; Hikmah, Nur; Fahira, Ainun; Satriani, Satriani (ETDC: Indonesian Journal of Research and Educational Review, 2022)
The purpose of this study is to determine whether or not using the directed reading thinking activity approach can enhance first-year MTs As'adiyah Putra 2 Sengkang students' reading comprehension of narrative texts. With an experimental class, this study used a pre-experimental design. Pre-test and post-testing were done as part of the data collection process. The first year of MTs As'adiyah Putra 2 Sengkang in the academic year 2020–2021 made up the population of this study. 32 students from the VII B class were used in the purposive sampling strategy to collect the sample. The research used multiple choice, true/false, and matching word questions as its instruments. The outcome of the data analysis revealed a substantial difference between the pre-test and post-test scores of the students. It was demonstrated by the statistical analysis's finding that the post-test score was higher than the pre-test (0.000 < 0.05), which was significant at the level of 0.05. The researcher draws the conclusion that using the directed reading thought activity strategy helps students' reading comprehension of narrative texts based on the analysis's findings.